PENGARUH BUDAYA ORGANISASI SEKOLAH, PENGALAMAN KERJA, DAN KOMPENSASI TERHADAP KEPUASAN, MOTIVASI KERJA, DAN KINERJA KEPALA SMA SE EKS KARESIDENAN SEMARANG - PPs Universitas Negeri Semarang, Sudharto (Jurnal Manajemen Pendidikan, 2012)
Abstract: Principles in the school-based management model absolutely play a central position with a wide, autonomous authority and a complex role. This research is aimed to know the direct and indirect influences of school organization cultures, work experiences, compensation towards principles, performance through work satisfaction and work motivation. This is a quantitative research of a path analysis model with ex post facto data conducted to 206 principles of Senior High School (SMA) through out Semarang and surrounding districts. The research results show that school organization cultures give the biggest contribution compared with another variables examined. The next sequences are: work satisfaction, motivation, compensation, work experience. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh budaya organisasi sekolah, pengalaman kerja, kompensasi terhadap kinerja kepala sekolah baik secara langsung maupun tidak langsung (melalui kepuasan kerja dan motivasi kerja). Subjek penelitian adalah 206 orang kepala SMA se eks Karesidenan Semarang. Penelitian ini menggunakan rancangan korelasional kausal. Pengumpulan data menggunakan angket. Data hasil penelitian dianalisis dengan path analysis. Hasil penelitian menunjukkan budaya organisasi sekolah pengaruhnya sangat dominan terhadap kinerja kepala sekolah jika dibanding dengan variabel lainnya yang diteliti. Urutan selanjutnya adalah kepuasan kerja, motivasi kerja, kompensasi, dan pengalaman kerja. Keywords: school organization, culture, work experiences, compensation, work satisfaction, motivation and performance.